DAMPAK PERLUASAN AREAL PADA KOMODITAS KARET TERHADAP PEREKONOMIAN PROVINSI JAMBI - Rizki Gemala Busyra (Departemen Ekonomi Sumberdaya dan Lingkungan, Fakultas Ekonomi dan Manajemen, Institut Pertanian Bogor, 2014)
Since 2006, commodity development in Jambi is focusing on rubber through area expansion, rejuvenation and plant rehabilitation. The scope of this research is to study the relation between plantation commodity development which done through area expansion and Jambi’s economy. The objectives of this study are to identify factors that influence the size of area, production, productivity, price and export of rubber in Jambi, as well as to analyze the impact of rubber expansion to Jambi’s economy. This study used secondary data, which compiled as annual pooled data, at nine districts in Jambi Province from 2000 to 2012. The analysis method used was simultaneous equation econometric, which consists of 2 identity equations and 5 structural equations, followed by model identification, model estimation using 2 SLS, validation and simulation of model. The model shows the relation between rubber expansion policy with Jambi’s economy where a 6% increase in expansion will increase the economy by 0.95%. Thus, it is recommended that Jambi Province remains focus on rubber expansion because it positively impacts their economic development.